Housing policy in Spain between 1939 and 1976: The residential phenomenon as a catalyst for urban growth - Navas-Carrillo, Daniel; Ostos-Prieto, Javier; Rodríguez-Lora, Juan-Andrés (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The research focuses on the study of public housing built in response to the urgent housing needs in Europe throughout the 20th century. These developments share many of the characteristics of their European counterparts. The Spanish case presents certain peculiarities in its development. The research aims to analyse the context -social, economic and political- that conditioned the massive construction of housing in Spain between 1939 and 1976. An analysis is made of the approved urban planning legislation, housing regulation and the identification of the responsible bodies.